SYNTHESIS, CHARACTERIZATION AND ANTI-INFLAMMATORY ACTIVITY OF NOVEL PYRAZOLE DERIVATIVES - P, HARATHI; V V S, RAJENDRA PRASAD; D, SATYAVATI; SUBRAMANIAN, SIVA; BOYA, VIVEKANANDA; GALI, PRASHANTHI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: To synthesize novel pyrazole derivatives and their evaluation for anti-inflammatory activity. Methods: The synthesis of chalcone (1) was carried out by using Claisen-Schmidt condensation. which on further cyclization with thiosemicarbazide gives the substituted 3, 5-diphenyl-4, 5-dihydro-pyrazole-1-carbothoic acid amide (2), further reaction with different aldehydes yield title compounds (3). Using this scheme 8 compounds were synthesized which further have been evaluated for anti-inflammatory activity by egg-albumin induced paw edema. Results: All the synthesized compounds have been supported by spectral analysis. The anti-inflammatory activity of synthesized compounds was compared with standard anti-inflammatory agent Diclofenac sodium. Conclusion: Compound-8, compound-2 and compound-3 showed greater anti-inflammatory activity due to the presence of alkene and electron withdrawing groups (Cl and NO 2 ). Keywords: Chalcone, Thiosemicarbazide, Pyrazole derivatives, Anti-inflammatory activity.